Evaluation of an Allosteric BACE Inhibitor Peptide to Identify Mimetics that Can Interact with the Loop F Region of the Enzyme and Prevent APP Cleavage. Issue 11 (25th May 2018) - Campagna, Jesus; Vadivel, Kanagasabai; Jagodzinska, Barbara; Jun, Michael; Bilousova, Tina; Spilman, Patricia; John, Varghese
Abstract: The aspartyl protease BACE1 (BACE) has emerged as an appealing target for reduction of amyloid-β in Alzheimer's disease. The clinical fate of active-site BACE inhibitors may depend on potential side effects related to enzyme and substrate selectivity. One strategy to reduce this risk is through development of allosteric inhibitors that interact with and modulate the Loop F region unique to BACE1. Previously, a BACE-inhibiting antibody (Ab) was shown by co-crystallization to bind and induce conformational changes of Loop F, resulting in backbone perturbations at the distal S6 and S7 subsites, preventing proper binding of a long APP-like substrate to BACE and inhibiting its cleavage. In an effort to discover small Loop F-interacting molecules that mimic the Ab inhibition, we evaluated a peptide series with a YPYF(I/L)P(L/Y) motif that was reported to bind a BACE exosite. Our studies show that the most potent inhibitor from this series, peptide 65007, has a similar substrate cleavage profile to the Ab and reduces sAPPβ levels in cell models and primary neurons. As our modeling indicates, it interacts with the Loop F region causing a conformational shift of the BACE protein backbone near the distal subsites. The peptide-bound enzyme adopts a conformation that closely overlays with the crystal structure (PDB: 3R1G ) from Ab binding. Importantly, peptide 65007 appears to be BACE substrate and enzyme selective, showing little inhibition of NRG1, PSGL1, CHL1, or Cat D. Thus, peptide 65007 is a promising lead for discovery of Loop F-interacting small-molecule mimetics as allosteric inhibitors of BACE. Graphical Abstract: Unlabelled Image